Better Outcomes for Older people with Spinal Trouble (BOOST) Trial: a randomised controlled trial of a combined physical and psychological intervention for older adults with neurogenic claudication, a protocol. Issue 10 (18th October 2018) - Williamson, Esther; Ward, Lesley; Vadher, Karan; Dutton, Susan J; Parker, Ben; Petrou, Stavros; Hutchinson, Charles E; Gagen, Richard; Arden, Nigel K; Barker, Karen; Boniface, Graham; Bruce, Julie; et al.
Abstract : Introduction: Neurogenic claudication due to spinal stenosis is common in older adults. The effectiveness of conservative interventions is not known. The aim of the study is to estimate the clinical and cost-effectiveness of a physiotherapist-delivered, combined physical and psychological intervention. Methods and analysis: This is a pragmatic, multicentred, randomised controlled trial. Participants are randomised to a combined physical and psychological intervention (Better Outcomes for Older people with Spinal Trouble (BOOST) programme) or best practice advice (control). Community-dwelling adults, 65 years and over, with neurogenic claudication are identified from community and secondary care services. Recruitment is supplemented using a primary care-based cohort. Participants are registered prospectively and randomised in a 2:1 ratio (intervention:control) using a web-based service to ensure allocation concealment. The target sample size is a minimum of 402. The BOOST programme consists of an individual assessment and twelve 90 min classes, including education and discussion underpinned by cognitive behavioural techniques, exercises and walking circuit. During and after the classes, participants undertake home exercises and there are two support telephone calls to promote adherence with the exercises. Best practice advice is delivered in one to three individual sessions with a physiotherapist. The primary outcome is the Oswestry Disability Index at 12 months. Secondary outcomes include the 6 Minute Walk Test, Short Physical Performance Battery, Fear Avoidance Beliefs Questionnaire and Gait Self-Efficacy Scale. Outcomes are measured at 6 and 12 months by researchers who are masked to treatment allocation. The primary statistical analysis will be by 'intention to treat'. There is a parallel health economic evaluation and qualitative study. Ethics and dissemination: Ethical approval was given on 3 March 2016 (National Research Ethics Committee number: 16/LO/0349). This protocol adheres to the Standard Protocol Items: Recommendations for Interventional Trials checklist. The results will be reported at conferences and in peer-reviewed publications using the Consolidated Standards of Reporting Trials guidelines. A plain English summary will be published on the BOOST website. Trial registration number: ISRCTN12698674 ; Pre-results.